Targeting neuroinflammation in Alzheimer's disease: from mechanisms to clinical applications - Si, Zi-Zhen; Zou, Chen-Jun; Mei, Xi; Li, Xiao-Fang; Luo, Hu; Shen, Yao; Hu, Jun; Li, Xing-Xing; Wu, Lun; Liu, Yu (Neural regeneration research, 2023)
Alzheimer's disease is characterized by sustained neuroinflammation leading to memory loss and cognitive decline. The past decade has witnessed tremendous efforts in Alzheimer's disease research; however, no effective treatment is available to prevent disease progression. An increasing body of evidence suggests that neuroinflammation plays an important role in Alzheimer's disease pathogenesis, alongside the classical pathological hallmarks such as misfolded and aggregated proteins (e.g., amyloid-beta and tau). Firstly, this review summarized the clinical and pathological characteristics of Alzheimer's disease. Secondly, we outlined key aspects of glial cell-associated inflammation in Alzheimer's disease pathogenesis and provided the latest evidence on the roles of microglia and astrocytes in Alzheimer's disease pathology. Then, we revealed the double-edged nature of inflammatory cytokines and inflammasomes in Alzheimer's disease. In addition, the potential therapeutic roles of innate immunity and neuroinflammation for Alzheimer's disease were also discussed through these mechanisms. In the final section, the remaining key problems according to the current research status were discussed.